(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The objective of this study was to obtain an insight into the role of the vascular endothelial growth factor (VEGF) in pregnancy-associated mammary epithelial development and angiogenesis. However, we examined the primary VEGF receptor (VEGFR-2) in the mouse mammary cycle. Materials and Methods: The virgin (10–12 weeks), days 10 and 18 of pregnancy (P-10 and P-18), days 0, 5, 10, and 20 of lactation (L-0, L-5, L-10, and L-20), and days 5 and 10 of post-weaning (W-5 and W-10) stage were all used in this study. Immunohistochemistry and Western blotting were carried out on mammary tissues taken from three mice at each stage. Results: VEGFR-2 was detected immunohistochemically in the cytoplasm of mammary epithelial and endothelial cells. Immunostaining for VEGFR-2 was consistently positive in mammary endothelial cells across all stages, whereas staining intensity in epithelial cells varied across the mammary cycle. Additionally, immunoblot analysis indicated a 220 kDa unique band of VEGFR-2 protein at all stages of the mammary cycle, with the maximum expression reported toward the end of pregnancy and gradually decreasing toward the end of lactation. Conclusion: In conclusion, the presence of VEGFR-2 in the mammary epithelium in addition to the endothelium suggests that VEGF plays an autocrine and paracrine role in the development, proliferation, and differentiation of the mammary epithelium during pregnancy. J. Adv. Vet. Anim. Res., 8(4): 581-588, December 2021 http://doi.org/10.5455/javar.2021.h548